Mainstreaming disability into the poverty reduction processes in Uganda : the role of the human rights - based approach to the National Development Plan - Mulumba, Moses (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Rehabilitation)--University of Stellenbosch, 2011.